Boron-doped hydrogenated mixed-phase silicon as thermo-sensing films for infrared detectors. (February 2018) - Phong Pham, Duy; Park, Jinjoo; Shin, Chonghoon; Kim, Sangho; Nam, Yonghyun; Kim, Geunho; Kim, Minsik; Yi, Junsin
Abstract: Silicon materials have been widely used as thermo-sensing layers in infrared detectors or uncooled micro-bolometers. Parameters such as a large thermal coefficient of resistance (TCR), low sheet resistance (Rs ), and low 1/f noise are important for high performance of these devices. However, there is always a trade-off between these parameters. For example, the crystalline silicon materials typically exhibit low Rs and 1/f noise, and significantly low TCR, while the amorphous silicon materials generally have large TCR, and considerably high Rs and 1/f noise. Consequently, the best trade-off can be achieved by using a mixed-phase structure of silicon materials, i.e. an intermediate form between the crystalline and amorphous structures. Herein we report the important characteristics of hydrogenated mixed-phase silicon films, deposited by the plasma-enhanced chemical vapour deposition process, for infrared detectors. The films in the mixed-phase structure showed high TCR values in the range of 2–3% K –1 and moderate sheet resistances in range of 10–40 MΩ sq −1 . These results indicate that the mixed-phase silicon films are potential alternatives to conventional boron doped hydrogenated amorphous and microcrystalline silicon films for use as thermo-sensing layers in infrared detectors.